Protective effects of Ginkgo biloba extract on cultured rat cardiomyocytes damaged by H2O2 - Niu Yu-hong; Yang Xue-yi; Bao Wei-sheng (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the influence of Ginkgo biloba extract (GbE) on cardiomyocytes damaged by H2O2. METHODS: Cultured rat cardiomyocytes were divided into 3 groups randomly: control group; H2O2 (2.5 mmol.L-1) group; H2O2 2.5 mmol.L-1 + GbE 150 mg.L-1 group. The cardiomyocytes were cultured in MEM (Eagle's) at 37 degrees C in the presence of 5% CO2 for 4 h. Lactate dehydrogenase (LDH) was assayed by colorimetric method. Lipid peroxidation was determined by measuring thiobarbituric acid-reactive substances. Ultrastructure was viewed under transmission electron microscope. RESULTS: Compared with the control group, LDH leakage and malondialdehyde (MDA) content increased in H2O2 group, LDH increased from (2166 +/- 247) U.L-1 to (5180 +/- 648) U.L-1, MDA increased from (3.5 +/- 0.2) nmol/10(6) cells to (7.2 +/- 0.4) nmol/10(6) cells (P < 0.01). The ultrastructure was damaged seriously. GbE inhibited the increase of LDH leakage and MDA content induced by H2O2. In this group, LDH decreased from (5180 +/- 648) U.L-1 to (3496 +/- 386) U.L-1, MDA decreased from (7.2 +/- 0.4) nmol/10(6) cells to (4.8 +/- 0.9) nmol/10(6) cells (P < 0.01). Ultrastructure of cells was also protected by GbE. CONCLUSION: GbE protected the cardiomyocyte against H2O2 injury, the protective action was attributed to its antiperoxidative effect.